Analisis Tindak Tutur Direktif dalam Video Pembelajaran Bahasa Indonesia pada Kanal YouTube Kejarcita - Alliya Setiawan Putri; Nurul Hikmah; Narista Amellea Dinata; Najwa Sakinah; Cynara Rahmania; Asep Purwo Yudi Utomo; Satsya Yoga Baswara; Ermawati Ermawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Learning media is one of the keys to achieving success in the learning process in the classroom. This research aims to obtain, examine, and discuss several utterances in Indonesian language learning videos on the Kejarcita YouTube channel. This research uses a methodological approach (qualitative approach) and a theoretical approach in the form of pragmatics (directive speech acts). The data source for this research was obtained from videos in the